A case of “distillation” of human heads in the Eighteenth Century for medicinal purposes resulting in calcination of the cranium - Porro, Alessandro; Biehler-Gomez, Lucie (Medicina Historica, 2024)
Carlo Gandini (1705-1788) is known for the introduction of typical traditional Chinese Medicine practices into Italian medicine, and in particular, that of pulsology. Yet, his activity led him to perform other interesting experimentations, among which, human head distillation. Distillation from human heads was performed since the 17th century and permitted the obtention of an elixir prescribed to treat encephalic diseases. In this paper, we present his analysis, the result of his experimentation and what appears to be the first evidence of cremation, albeit unintentional, some one hundred and forty years before the first modern cremations.